Etude théorique et expérimentale d’un mur capteur type TROMBE - GUEMARI, Elhadi; Ghendir mabrouk youcef, youcef (جامعة الوادي University of Eloued, 2017)
كان استخدام الطاقة الشمسية في مجال الإسكان مع انخفاض استهلاك الطاقة موضوع العديد من الدراسات وقد وضعت في فرنسا من قبل أستاذ ترومب تقنية التدفئة على أساس نظام لجمع وتخزين واسترداد الحرارة الشمسية. جدار ترومب هو بسيط ومثيرة للاهتمام للقبض على نظام الطاقة الشمسية. وهو يتألف من اجدار البناء الثقيلة التي تواجه الجنوب، مع اثنين من فتحات للدوران الهواء بين المحلي والمسببة للاحتباس الحراري التي شكلتها سطح المتلقي من الجدار وغطاء زجاجي شفاف للإشعاع محاصرة الحادث الشمسي. جدار الاستشعار ينقل الطاقة الشمسية الملتقطة بطريقتين جزء ينتقل عن طريق التوصيل من خلال جدار يعيد إلى داخل الغرفة من قبل الحمل الحراري، في حين ينتقل الجزء الثاني من دوران الهواء الطبيعي الساخنة وجدت في المدخنة الشمسية من خلال فتحات. في هذه الدراسة، ستتم معالجة جزئيين رئيسيين. دراسة النظرية التي تركز على المعلمات التي تحدث أثناء عملية الجدار الاستشعار. دراسة تجريبية في الشركة TCCE، التي من خلالها سنحاول تحقيق الجدار الشمسية وتسليط الضوء على أهمية هذا استهلاك الطاقة بسيطة وفعالة واقتصادية في مجال الإسكان القائم، لا سيما في المناطق القاحلة وشبه - القاحلة التي تتميز بمناخ جاف وبارد في فترة الشتاء. L’utilisation de l’énergie solaire dans le domaine de l’habitat à faible consommation énergétique a fait l’objet de nombreuse études.une technique de chauffage se basant sur un système de captation solaire, de stockage et de restitution de la chaleur a été développée en France par le professeure Trombe. Le mur Trombe est un système simple et intéressant de captage de l’énergie solaire. Il est constitué d’un mur vertical en maçonnerie lourde orienté vers le sud, muni de deux orifices permettant la circulation de l’air entre le local et la serre formée par la surface réceptrice du mur et la couverture transparente en verre pour piégeage du rayonnement solaire incident . le mur capteur transmet l’énergie solaire captée par deux moyens une partie est transmise par conduction à travers le mur qui la restitue à l’intérieur du local par convection et rayonnement alors que la deuxième partie se transmet par la circulation naturelle de l’air chaud se trouvant dans la cheminée solaire à travers les orifices. Dans la présente étude, deux principales parties seront traitées ; une étude théorique qui s’intéresse aux paramètres qui intervient durant le fonctionnement du mur capteur. Une étude expérimentale au sein de la société CCTE, à travers laquelle on essayera de réaliser le mur trombe et de mettre en évidence l’importance de cette technique simple, efficace et économique dans l’habitat à base consommation énergétique, notamment dans les zones arides et semi – arides qui sont caractérisés par un climat sec et froid en période d’hiver. Abstract: The use of solar energy in housing with low energy consumption has been the subject of many studies and has been developed in France by Professor Trump heating technique based on the system for collection, storage and recovery of solar heat. The Trump wall is simple and interesting to capture the solar system. It consists of a heavy construction wall facing the south, with two openings for air circulation between the local and greenhouse formed by the receiving surface of the wall and a transparent glass cover for radiation trapping the solar incident. The wall of the sensor transmits solar energy captured in two ways. A part transmitted by conduction through a wall reverts into the chamber by convection, while the second part of the hot natural air circulation is found in the solar chimney through the openings. In this study, two main parts will be addressed. A theoretical study focusing on the parameters that occur during the wall sensor process. A pilot study at TCCE, through which we will try to achieve the solar wall and highlight the importance of this simple, efficient and economical energy consumption in existing housing, especially in arid and semi-arid regions characterized by dry and cold climate in winter. The use of solar energy in the field of energy-efficient housing has been the subject of numerous studies. A heating technique based on a solar capture, heat storage and Developed in France by Professor Trombe. The Trombe wall is a simple and interesting system for collecting solar energy. It consists of a vertical masonry wall facing south, provided with two orifices allowing the circulation of the air between the room and the greenhouse formed by the receiving surface of the wall and the transparent cover of glass for trapping radiation Solar incident. The sensor wall transmits the solar energy captured by two means, a part is transmitted by conduction through the wall which returns it to the interior of the room by convection and radiation while the second part is transmitted by the natural circulation of the air Hot in the solar chimney through the holes. In this study, two main parts will be addressed; A theoretical study that focuses on the parameters that occur during the operation of the sensor wall. An experimental study within the CCTE company, through which we will try to realize the torn wall and to highlight the importance of this simple, efficient and economical technique in the habitat based on energy consumption, especially in the arid zones And semi - arid regions which are characterized by a dry and cold climate during winter. Abstract The use of solar energy in housing with low energy consumption has been developed in France by Professor Trump. The Trump wall is simple and interesting to capture the solar system. It consists of a heavy construction wall facing the south, with two openings for air traffic between the local and greenhouse, formed by the receiving surface of the wall. The wall of the sensor transmits solar energy captured in two ways. A part of the solar chimney through the openings is the second part of the hot natural air circulation. In this study, two main parts will be addressed. A theoretical study focusing on the parameters that occur during the wall sensor process. A pilot study at CITT, through which we will try to achieve the solar wall and highlight the importance of this simple, efficient and economical energy consumption in particular housing, especially in arid and semi-arid regions
مذكرة ماستر هندسة ميكانيكية تخصص طاقات متجددة